Respiratory Endoscopy - Izumo, Takehiro; Sasada, Shinji; Aso, Tomohiko; Nasu, Kazuko; Arai, Yasuaki (Springer Singapore : Imprint: Springer, 2017)
This book provides a detailed overview of the latest innovations in respiratory endoscopy, from both diagnostic and therapeutic perspectives; each chapter focuses on one disease and the techniques for early diagnosis as well as treatment. It comprehensively covers treatment and procedures, including simultaneous X-ray fluoroscopy and its use during bronchoscopic procedures. This fast-developing technology is essential for the medical management of non-malignant and malignant diseases of the chest, especially lung cancer. Respiratory Endoscopy describes the cooperation between all the members of the healthcare team, and as such is a valuable resource not only for medical staff, but also for radiological technicians and nursing staff who contribute significantly in the care of the patients undergoing these invasive procedures. By promoting teamwork and providing practical know-how, it will improve the success and safety of respiratory endoscopy procedures.
Keywords: Medicine.; Radiology.; Respiratory organs -- Diseases.; Oncology.; Nursing.; elektronické knihy; electronic books